The ATM Cofactor ATMIN Protects against Oxidative Stress and Accumulation of DNA Damage in the Aging Brain - Kanu, Nnennaya (American Society for Biochemistry and Molecular Biology, 2010)
Progressive accumulation of DNA damage is causally involved in cellular senescence and organismal aging. The DNA damage kinase ATM plays a central role in maintaining genomic stability. ATM mutations cause the genetic disorder ataxia telangiectasia, which is primarily characterized by progressive neurodegeneration and cancer susceptibility. Although the importance of ATM function to protect against oxidative DNA damage and during aging is well described, the mechanism of ATM activation by these stimuli is not known. Here we identify ATM interactor (ATMIN) as an essential component of the ATM signaling pathway in response to oxidative stress and aging. Embryos lacking ATMIN (atmin(Δ/Δ)) died in utero and showed increased numbers of cells positive for phosphorylated histone H2aX, indicative of increased DNA damage. atmin(Δ/Δ) mouse embryonic fibroblasts accumulated DNA damage and prematurely entered senescence when cultured at atmospheric oxygen levels (20%), but this defect was rescued by addition of an antioxidant and also by culturing cells at physiological oxygen levels (3%). In response to acute oxidative stress, atmin(Δ/Δ) mouse embryonic fibroblasts showed slightly lower levels of ATM phosphorylation and reduced ATM substrate phosphorylation. Conditional deletion of ATMIN in the murine nervous system (atmin(ΔN)) resulted in reduced numbers of dopaminergic neurons, as does ATM deficiency. ATM activity was observed in old, but not in young, control mice, but aging-induced ATM signaling was impaired by ATMIN deficiency. Consequently, old atmin(ΔN) mice showed accumulation of DNA damage in the cortex accompanied by gliosis, resulting in increased mortality of aging mutant mice. These results suggest that ATMIN mediates ATM activation by oxidative stress, and thereby ATMIN protects the aging brain by preventing accumulation of DNA damage.